Law Enforcement of Civil Servants Who Violate Marriage/Divorce Permissions - Hariati, Sri; Haeratun (International Journal of Law Analytics, 2024)
Regarding sanctions for civil servants who divorce without obtaining prior permission, they are applied in terms of law enforcement for civil servants who prohibit divorce permits in Article 15 of Government Regulation Number 45 of 1990 concerning Amendments to Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants apparently still very weak, this is proven by two government employees who violated disciplinary regulations because they entered into a second marriage without permission from their superiors, only one person has been sentenced to discipline, and there are two female civil servants who served as first and second wives. Those who divorce without permission from officials have not been given any sanctions by the authorized officials.